Performance Analysis of Large-Scale Digital Phased Array Mixed-ADC Receiver in Compact Space - ZHANG Yi; GAO Hang; MA Song; GUO Hongru; XIA Bin; ZHANG Chaoxian (天地一体化信息网络)
In order to evaluate the performance of large-scale digital phased array mixed-ADC receivers under the influence of mutual coupling effects in compact spaces, a performance analysis method was proposed. Firstly, the propagation channel under the influence of mutual coupling effects was modeled by jointly considering the three-dimensional channel model, mutual coupling effect model, and ADC quantization noise model. Then, used a linear maximum ratio combining receiver and based on random matrix theory, a closed form expression for the achievable rate of the system under a given antenna array topology was derived. Finally, the achievable rates of uniform linear arrays and uniform planar arrays under different mixed-ADC configurations were theoretically calculated and numerically simulated. The calculation and simulation results both indicated that optimizing the mixed-ADC configuration scheme could effectively improve the system achievable rate, and the conclusion could provide theoretical support for the design of high achievable rate mixed-ADC receivers in compact spaces.